2017
DOI: 10.4172/1948-5956.1000504
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Clinicopathological Characteristics of Breast Cancer at Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia

Abstract: Breast cancer (BC) is one of the most heterogeneous types of cancer and is characterized by several molecular subtypes. Descriptive cross-sectional study was conducted on 137 confirmed BC cases at Tikur Anbessa Specialized Hospital (TASH) in Ethiopia from December 2015 to November 2016 to assess the biological and clinicopathological characteristics of BC in Ethiopian women patients. Socio-demographic characteristics of the study subjects was obtained with pretested structured interview and clinical data was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 42 publications
(48 reference statements)
7
13
0
Order By: Relevance
“…The sampling strategy was to obtain a number of cases necessary for statistical significance of the results. The size of our sample of 150 cases is closer to several studies [9,10,19,20] and significantly superior to other studies [21,22] .…”
Section: Discussionsupporting
confidence: 49%
“…The sampling strategy was to obtain a number of cases necessary for statistical significance of the results. The size of our sample of 150 cases is closer to several studies [9,10,19,20] and significantly superior to other studies [21,22] .…”
Section: Discussionsupporting
confidence: 49%
“…This was in line with the study conducted by Hadgu et al 11 at Tikur Anbessa Specialized Hospital (TASH) on 114 breast cancer patients (mean age = 43 years and median age = 40 years). Another study done by Shenkutie et al 15 at TASH on 137 breast cancer cases (mean age = 47 years and median age = 46.7 years) was also in line with the current findings. Similar studies from Libya and Rwanda research groups were also reported that median age of 45 and 49 years, respectively, which were not considerably far away from this study.…”
Section: Discussionsupporting
confidence: 92%
“…These study findings were comparable with study done at TASH that 45% of cases had tumor size (T2 = 47.5%) greater than 2 cm and less than 5 cm; 51% had grade II and 35.4% grade III tumors. 15 Another previous study in Ethiopia by Gemta et al 23 reported that 47.2% of case had tumor size (T2) and 17.3% and 46.2% of cases present with grade I and grade II tumors, respectively. In this study, only 2.5% of patients had tumor size (T3) greater than 5 cm.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Additionally, data from this population shows that patients with a family history were more likely to be ER-than patients without a family history (19), suggesting that many of these patients’ cancers are due to somatic mutations. We also searched for mutations in genes related to breast cancer aggression, subtype, and progression.…”
Section: Resultsmentioning
confidence: 88%